On the probabilities of large deviations for sums of random number of independent random variables - Statulevičius, V. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. А. Статулявичюс. О вероятностях больших уклонений для суммы случайного числа независимых случайных величинV. Statulevičius. Didelių atsilenkimų tikimybių nepriklausomų atsitiktinių dydžių sumai su atsitiktiniu dėmenų skaičiumi klausimu